If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 3 + q Solving 0 = 3 + q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-1q' to each side of the equation. 0 + -1q = 3 + q + -1q Remove the zero: -1q = 3 + q + -1q Combine like terms: q + -1q = 0 -1q = 3 + 0 -1q = 3 Divide each side by '-1'. q = -3 Simplifying q = -3
| 1+x^3=1.5 | | x-10+2x-34= | | -5(4x-2)=32 | | 4x^2-79=2 | | (-5/3)/(3/8) | | y=-2.5-3/2x | | 5g+3g-10+6=8g+12 | | 3(2p-2)+2(5p-10)=8p+9 | | 6a^2=-5a+13 | | x^2-41x-392=0 | | x*x+x=(x+1)-(x+1) | | -6c-9c=28 | | -7x-5=6 | | s+10=6 | | -5-3+4x+1=-4 | | 2y-4x=o | | 7lnx-6=3 | | X^4-4x^3+8x^2-12x+15=0 | | 5M=-2M-44/4 | | 2=(x/4)-11 | | 5t+9.2=19.7 | | -5z+4+3z=30 | | 2lnx=36 | | x/-7.6=3.06 | | 3/5y=-3 | | 1/2g-4=20 | | 8.5x-2.5forx=3 | | 42=2x+14 | | 9(t+21)=3(t-2) | | 1-3x=2x(x+5) | | 8(7n+4)-5n=n-18 | | 2y-3.1=1.7 |